The influence of work motivation on employee loyalty: the mediating role of job satisfaction at pt alido ps - Muhammad Gilang Ramadhan; Anna Suzana (Jurnal Mantik, 2026)
Employee loyalty plays a crucial role in ensuring organizational sustainability and competitiveness. However, previous studies have reported inconsistent findings regarding the mediating role of job satisfaction in the relationship between work motivation and employee loyalty, while empirical evidence from Indonesia's poultry industry remains limited. This study aimed to examine the direct effect of work motivation on employee loyalty and the indirect effect through job satisfaction at PT Alido PS. A quantitative approach with an associative causal design was employed involving 101 employees selected through simple random sampling from a population of 200 employees. Data were collected using structured questionnaires and analyzed using path analysis, Sobel testing, and Variance Accounted For (VAF). The results revealed that work motivation significantly influenced job satisfaction (? = 0.662, p < 0.001) and employee loyalty (? = 0.418, p < 0.001), while job satisfaction also had a significant positive effect on employee loyalty (? = 0.422, p < 0.001). The indirect effect of work motivation on employee loyalty through job satisfaction was 0.279, with a Sobel test value of 4.11, confirming a significant mediation effect. The VAF value of 40% indicated partial mediation, while the coefficient of determination (R² = 0.768) showed that the proposed model explained 76.8% of the variance in employee loyalty. This study contributes to the human resource management literature by providing empirical evidence that job satisfaction partially mediates the relationship between work motivation and employee loyalty in the underexplored context of Indonesia's poultry industry. The findings also offer practical insights for organizations seeking to strengthen employee loyalty through integrated strategies that enhance both work motivation and job satisfaction.